Analysis of domestic prosumer influence on a smartgrid - Carvalhuco, João (2019)
The shift from a centralized production to a distributed generation based on renewable energy production has been increasing, resulting in prosumer arising as new stakeholder of the electrical system. In this paper, a prosumer that owns photovoltaic solar panels and small wind generator, is considered and renewable energy production forecast is given by artificial neural networks (ANN). An energy management model is developed considering a battery storage system. Several case studies are analyzed considering seasonality factors.